Indulgent Parenting and Adolescents' Maladjustments: The Roles of Cultural Context and Parental Gender - Qinglan Feng; Yanyun Yang; Ming Cui (MDPI AG, 2024)
Background/Objectives. Adolescence is a critical developmental stage marked by the exploration of independence and self-identity. In this study, we aimed to examine the association between indulgent parenting (characterized by high responsiveness and low demandingness) and adolescents' maladjustments across emotional, behavioral, and social domains. Methods. Using a cross-cultural sample of high school students from the U.S. (n = 268) and China (n = 189), we tested the hypotheses that indulgent parenting was associated with adolescents' maladjustments, and that such association varied by cultural context (U.S. vs. China) and parental gender. Results. The results from Bayesian structural equation modeling supported the hypotheses, showing significant associations between indulgent parenting and adolescents' maladjustments and differences in the associations across cultures and parental gender. Conclusions. The findings highlighted the need for culturally informed parenting programs to foster healthy adolescent development.